Co‐Creating Multilingual Books with Children to Foster Their Literacies. (15th December 2021) - Harris, Pauline; Camaitoga, Ufemia; Brock, Cynthia H.; Diamond, Alexandra; McInnes, Elspeth; Neill, Bec
Abstract: This article describes how young children and their families and community members came together with researchers to co‐create books in children's languages about their worlds in Fiji, to foster children's multilingual literacies. The co‐creation of these books in children's and families' Fijian homes and community settings connected with their voices, languages, and literacies, to ensure both the books and the processes for co‐creating them would be culturally sustaining and effective for children's multilingual literacy growth. Among the research team here, two were based in Fiji and the rest were based in Australia. We learned many lessons in our journey from preschools and classrooms in Australia to children's homes and communities in Fiji, which we bring back to share with teachers internationally through The Reading Teacher .